PENGARUH KEBIJAKAN DIVIDEN PADA MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI MODERASI - Dahayani, Ni Ketut Sri; Budiartha, I Ketut; Suardikha, I Made Sadha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
The purpose of this study is to provide empirical evidence about the effect of dividend policy on earnings management and to determine whether the Good Corporate Governance (GCG) able to moderate dividend policy relationship with earnings management. The study population was banking companies listed in Indonesia Stock Exchange (BEI) in the period 2007-2014. Samples were determined using purposive sampling method. The samples selected were 8 2 banks observations. Data analysis technique used is Moderated Regression Analysis (MRA), first performed factor analysis to determine the factors GCG. Based on the analysis, this study proves that the dividend policy effect on earnings management. The results also showed that corporate governance is not proven able to moderate dividend policy relation to earnings management.
Keywords: Good Corporate Governance (GCG), Dividend Policy, Earning Management